Understanding the Role of Culture and Behavior in Mongolia’s Foreign Policy (Mongolian Journal of International Affairs, 2025)
This study explores how Mongolia, a small state located between Russia and China, integrates cultural and behavioral factors into its foreign policy. With a deep-rooted nomadic heritage and strong spiritual traditions, Mongolia emphasizes national identity, respect, and consensus in its diplomatic conduct. The research applies Hofstede’s cultural dimensions, the Big Five personality traits model, and a systematic literature review of Mongolian, Russian, and foreign sources to assess the role of culture and behavior in foreign policy. Findings reveal that Mongolia leverages cultural diplomacy by promoting its heritage through festivals, exhibitions, and international cooperation in culture, education, and science. These efforts also support tourism and foster soft power. Mongolia’s openness to other cultures, combined with values such as unity, justice, and respect, informs a diplomatic style focused on mutual understanding and balanced engagement. Behavioral coherence and intercultural sensitivity enhance Mongolia’s ability to navigate international relations despite limited economic or military power. The study underscores that Mongolia’s foreign policy is shaped not only by strategic interests but also by deeply ingrained cultural and behavioral traits. As global dynamics shift, Mongolia’s unique approach helps it maintain sovereignty, build partnerships, and strengthen its international presence.